Cultivating Opportunities for Faster Rural Income Growth and Poverty Reduction : Mozambique Rural Income Diagnostic - World Bank (Washington, DC: World Bank, 2022)
Mozambique’s economy has experienced strong growth over the last two decades, with GDP expanding at an annual average rate of 7.2 percent. However, this growth has been unequally shared and rural areas still lag far behind urban centers in both monetary and non-monetary dimensions of wellbeing. As most poor households live in rural areas, increasing rural incomes is essential to reducing poverty and ensuring the benefits of growth are distributed more equally. Income growth opportunities for rural poor households in Mozambique in the next 5-10 years are predominantly in the agricultural sector. Smallholder farming is the chief activity for most rural households, with income from non-farm sources and migration playing a lesser role and often constrained to specific regions. However, low levels of agricultural productivity, low participation in input and output markets, and high vulnerability to seasonality factors and shocks inhibits the capacity of rural households to increase their incomes. This report proceeds as follows: After setting out the framework and methods in more detail in section two, the following section provides some context by detailing the income, assets, and market engagements of rural households in Mozambique, focusing on a characterization of the livelihoods of the rural bottom 40 percent. Section four discusses the opportunities for growth across the main three sources of rural income (farm, non-farm, and migration). Section five then presents the main barriers to taking advantage of these opportunities, detailing the evidence behind this prioritization for the three most binding set of constraints. From this list of priority constraints, policy actions and investments to address the top three groups of binding constraints are discussed.